Ambiguous subjects: Obstetric violence, assemblage and South African birth narratives - Chadwick, Rachelle (Feminism & psychology, 2017)
Obstetric violence is gaining recognition as a worldwide problem manifesting in a range of geopolitical contexts. While global public health attention is turning to this issue, there has been a lack of theoretical engagement by feminist psychologists with the phenomenon of obstetric violence. This paper contributes to the literature on obstetric violence via a feminist social constructionist analysis of “marginalized” and low-income South African women’s narratives of giving birth in public sector obstetric contexts. Drawing on interviews conducted in 2012 with 35 black, low-income women living in Cape Town, South Africa, the analysis focuses on obstetric violence as a relational, disciplinary, and productive process that has implications for the construction of women’s subjectivities and agency during childbirth. The findings focus on relational constructions of violence and agency in women’s narratives, including (a) the performance of docility as an act of ambiguous agency and (2) resistant bodies and modes of discipline. Framed within a Foucauldian approach to power and using the concept of assemblage, I argue that obstetric violence needs to be conceptualized as more than isolated acts involving individual perpetrators and victims. Instead, the analysis shows that obstetric violence functions as a mode of discipline embedded in normative relations of class, gender, race, and medical power.